Librarians' Literacy in the Ethical Use of Artificial Intelligence for Research in the State University Libraries in South-South, Nigeria - Dime , Ishioma Angela; Ijiekhuamhen, Osaze Patrick (Brawijaya University Library, 2026)
The exponential growth of Artificial Intelligence (AI) has transformed academic research, positioning librarians in university libraries as central figures in navigating its ethical landscape. This study examined librarians' literacy in the ethical use of AI for research in state university libraries in South-South Nigeria. Adopting a descriptive survey design, the study utilized a total enumeration sampling technique to include all 164 librarians in the region, with 148 responding to an online questionnaire. Data were analyzed using mean scores and Pearson Product-Moment Correlation. Findings revealed that librarians possess a moderate level of AI ethics literacy (x̄ = 2.55), yet the actual application of ethical AI practices is low (x̄ = 2.37). The usage of specialized AI research tools remains low, with a preference for general tools like Google Scholar, Grammarly, and ChatGPT. Key challenges hindering ethical AI use include erratic power supply, poor internet bandwidth, and a lack of institutional AI policies. A strong positive correlation (r = 0.641) was found between AI ethics literacy and the quality of research support, indicating that higher ethical literacy leads to better service delivery. The study concludes that while conceptual awareness exists, structural and policy frameworks are urgently needed to translate this awareness into professional practice.